Impact Of Institutional And Regulatory Adjustment On Fdi Flows In Algeria - Graiche, Lynda (جامعة الوادي University of Eloued, 2025)
The purpose of this study is to examine the evolution of the regulatory and institutional framework, as well as its impact on Algeria's attractiveness, and more specifically on FDI flows. In so doing, we highlight the contributions of the new regulations and the challenges still to be met for better integration into the global economy. Based on an in-depth literature search on the articles of law and their impact on FDI movements, and an analytical descriptive method, the study revealed a number of findings, including that the new regulations have brought about positive changes in the economic dynamics of foreign direct investment (FDI) in several sectors. However, there are still some shortcomings that stand in the way of more effective attractiveness.
مقال
Keywords: FDI; attractiveness; economic policy; regulations; institutions.